2010
DOI: 10.1128/jvi.00387-10
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Continues To Replicate and Evolve in Patients with Natural Control of HIV Infection

Abstract: Elucidating mechanisms leading to the natural control of HIV-1 infection is of great importance for vaccineWe studied a cohort of 21 HIV-1 controllers with a median level of viremia below 1 copy/ml, followed for a median of 11 years. Less than half of the cohort carried known protective HLA types (B*57/27). By isolating HIV-1 RNA from large volumes of plasma, we amplified single genome sequences of both pro-rt and env longitudinally. This study is the first to document that HIV-1 pro-rt and env evolve in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 65 publications
(86 reference statements)
7
85
0
Order By: Relevance
“…In contrast, in patients on maximally suppressive therapy, evolution of viral genomes is frozen at the point at which therapy began (Ruff et al 2002;Tobin et al 2005), and no evidence for continuing evolution can be seen even after many years. In patients for which therapy is partially suppressive, ongoing evolution can still be observed (Tobin et al 2005), as is also true in patients known as "elite controllers," who naturally control HIV-1 infection at levels similar to those seen in patients on suppressive antiviral therapy (Mens et al 2010). The apparent lack of evolution on therapy is consistent with the absence of new cycles of infection.…”
Section: Persistence Of Hiv-1 Infection On Therapysupporting
confidence: 61%
“…In contrast, in patients on maximally suppressive therapy, evolution of viral genomes is frozen at the point at which therapy began (Ruff et al 2002;Tobin et al 2005), and no evidence for continuing evolution can be seen even after many years. In patients for which therapy is partially suppressive, ongoing evolution can still be observed (Tobin et al 2005), as is also true in patients known as "elite controllers," who naturally control HIV-1 infection at levels similar to those seen in patients on suppressive antiviral therapy (Mens et al 2010). The apparent lack of evolution on therapy is consistent with the absence of new cycles of infection.…”
Section: Persistence Of Hiv-1 Infection On Therapysupporting
confidence: 61%
“…Interestingly, in studies that followed these patients over a 5-year period, it was found that evolution of proviral clones in peripheral CD4 + T cells was rare, whereas significant evolution due to synonymous mutations was seen in plasma clones from the same patients over the same period of time [19]. Evolution of plasma virus has been confirmed in another cohort of ECs [20] whereas no evolution was seen in plasma viral clones in patients on cART using the same methods [21]. The data suggest that there is a greater degree of ongoing viral replication in ECs than in patients on cART.…”
Section: Defining the Reservoir In Ecsmentioning
confidence: 63%
“…Chronic progressors (CP) fall between these extremes and are generally placed on antiretroviral therapy when CD4 + T-cell counts drop to a clinically defined threshold. Elite suppressors (ES), in contrast, naturally control viremia to <50 copies/mL and usually maintain normal CD4 + T-cell counts (1,2), despite ongoing viral replication (3)(4)(5). Initial studies suggested that infection with replication-deficient virus was responsible for control of viremia in ES.…”
mentioning
confidence: 99%